2008
DOI: 10.1111/j.1440-1681.2008.04940.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinaemia‐induced Cardiovascular Changes in Rats

Abstract: (1) Increased plasma homocysteine content and increased blood pressure are independently associated with higher cardiovascular risks. The present study was designed to determine the effects of hyperhomocysteinaemia (HHcys) on the activity of the cardiovascular system in rats. (2) Using male Wistar rats, the effect of moderate HHcys, induced by treating rats with dl-homocysteine thiolactone (DL-HT; 1 g/kg per day) for 15 days, on arterial blood pressure, heart rate, baroreflex and vascular reactivity was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
1
9
1
Order By: Relevance
“…[26][27][28] In addition, our results demonstrated that HcyT treatment did not change heart weight and LV mass, but there was an important reduction in the FS.…”
Section: Discussionmentioning
confidence: 67%
“…[26][27][28] In addition, our results demonstrated that HcyT treatment did not change heart weight and LV mass, but there was an important reduction in the FS.…”
Section: Discussionmentioning
confidence: 67%
“…HCY, a sulfur amino acid which is synthesized from dietary methionine by a process of demethylation [ 30 ], has been demonstrated to be closely involved in the abnormal cardiovascular autonomic control and increased arterial pressure [ 31 ]. Increase in resting BP caused by hyperhomocysteinemia was totally reversed by interference with β 1-adrenoceptor antagonist atenolol, indicating that the HCY-relative hypertension is associated with the increase in sympathetic activity [ 32 ]. It has been well established that ROS has a pivotal role in the activation of the central and peripheral sympathetic nerve system [ 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our present data demonstrate that folate deficiency potentiates age-related increases in acetylcholine levels in the hearts of adult rats. Studies in rats [9, 10, 31, 32, 52, 53] and humans [5457] show that folate deficiency results in hyperhomocysteinemia, which, in turn, is associated with the risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%